Comparison of sex ratio in seurukan fish (Osteochilus vittatus) with different temperature induction - Alfis Syahril; Fazril Saputra; M. Barru Airil Fizra Hasibuan; Khairul Samuki; Cut Widy Aulia Putri (Universitas Malikussaleh, 2026)
Female seurukan fish exhibit relatively slow growth compared to male seurukan. Therefore, the application of simple genetic reproduction technology through reversal sex could be a solution to this problem. The research was conducted from August to December 2025 at the Mina Mandiri Research Institute (UPR Mina Mandiri), Beutong District, Nagan Raya Regency, and the Aquaculture Systems and Environment Laboratory, Faculty of Fisheries and Marine Sciences, and the Hatchery of the Faculty of Fisheries and Marine Sciences, Teuku Umar University, West Aceh. This study used five treatments and three replications: P0: treatment without immersion at 28oC, P1: immersion treatment at the embryonic phase at 30oC, P2: immersion treatment at the embryonic phase at 32oC, P3: immersion treatment at the larval phase at 30oC, and P4: immersion treatment at the larval phase at 32oC. The results showed that different temperature and time immersions had a significant effect (P<0.05) on the degree of hatching and sex identification, but did not affect the level of abnormality and survival rate of seurukan fish. Treatment P2 was the optimal treatment with a hatching rate percentage of 86.33±2.08% and sex identification of 80±0.00%. Keywords: Embryonic; Larvae; Seurukan Fish (Osteochilus vittatus); Sex Reversal; Temperature